2016
DOI: 10.4103/0250-474x.180244
|View full text |Cite
|
Sign up to set email alerts
|

Oral dispersible system: A new approach in drug delivery system

Abstract: Dosage form is a mean used for the delivery of drug to a living body. In order to get the desired effect the drug should be delivered to its site of action at such rate and concentration to achieve the maximum therapeutic effect and minimum adverse effect. Since oral route is still widely accepted route but having a common drawback of difficulty in swallowing of tablets and capsules. Therefore a lot of research has been done on novel drug delivery systems. This review is about oral dispersible tablets a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 16 publications
0
60
0
2
Order By: Relevance
“…48 and 0.55 g/cm 3 ), DT (between 0.55 and 0.65 g/cm 3 ), and Carr's compressibility index (between 12 and 26) given in (Table 2). The results of angle of repose and compressibility indicated that the flowability of powder blend is significantly good.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 and 0.55 g/cm 3 ), DT (between 0.55 and 0.65 g/cm 3 ), and Carr's compressibility index (between 12 and 26) given in (Table 2). The results of angle of repose and compressibility indicated that the flowability of powder blend is significantly good.…”
Section: Resultsmentioning
confidence: 99%
“…Oral route is undoubtedly the most important drug delivery route which offers various advantages like convenience of self-administration and easy manufacturing along with saving costs. [1][2][3] However many patients, especially geriatrics have dysphagia or difficulty in swallowing tablets and hard gelatin capsules and skip their prescribed medication, thus resulting in improper treatment. In these cases, orally disintegrating tablets (ODTs) have been found to be greatly useful.…”
Section: Introductionmentioning
confidence: 99%
“…SD refers to the group of solid products consisting of at least two different components, generally a hydrophilic matrix and a hydrophobic drug; the matrix can be either crystalline or amorphous [1]. The solid dispersion was introduced to overcome the low bioavailability of lipophilic drugs by forming a eutectic mixture of drugs with water soluble carriers.…”
Section: Solid Dispersionsmentioning
confidence: 99%
“…Fast dissolving tablets are also applicable when local action in the mouth is desirable such as local anesthetic for toothaches, oral ulcers, cold sores, or teething, and to those who cannot swallow intact sustained action tablets/capsules. The rate of absorption and the extent of bioavailability for such insoluble hydrophobic drug are controlled by the rate of dissolution [1]. Hence, an attempt has been made to increase the dissolution of such poorly water soluble drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The fast-dissolving tablets (FDTs) disintegrate and dissolve within seconds and are meant for administration to the patients who cannot swallow, such as elderly patients, stroke victims, bedridden patients, patients affected by renal failure, and patients who refuse to swallow, such as pediatric, geriatric, and psychiatric patients [3]. Hence, the present study was aimed at preparation of fast dissolving tablets of Pitavastatin using super disintegrant (Indion414) [4] and sublimating agent (camphor) [5] by direct compression method following 3 2 factorial design for the best-optimized formulation to increase dissolution of the drug, further to enhance absorption and bioavailability of drug for treating emergency clinical conditions of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%